KAJIAN ILMIAH IKAN GAR, FAMILI LEPISOSTEIDAE (Lepisosteus spp. & Atractosteus spp.): SPESIES ANCAMAN BAGI IKAN ASLI INDONESIA - Hadiaty, Renny Kurnia (ZOO INDONESIA, 2007)
Hadiaty, R.K. 2007. Scientific review of Gars, Family Lepisosteidae (Lepisosteusspp. & Atractosteus spp.): threat species for native Indonesian fish . ZooIndonesia 16 (2): 87-96. Indonesia is known as one of the countries with high fishdiversity. There are a lot of unexplore area which possibly have some undescribespecies. Damaging environment, poisoning and introduce species are very dangerousfor the sustainability of the native fish species in Indonesia. Gars are the alientpredator fish which prohibited to enter Indonesian waters since 1982, but the factsthere are many breeders of this species. This review paper is to discus the description,taxonomical history and the biology of gars. The aim of this paper is to build theawareness on the dangerous and destructive of this fish for Indonesian native species